Heat treatment and wounding as abiotic stresses to enhance the bioactive composition of pineapple by-products - Santos, Diana I. (2021)
Abiotic stress, like heat treatment and wounding, applied to pineapple by-products induce the accumulation of new compounds and add value. In this work the effect of the individual or combined application of wounding and heat treatment stresses on total phenolic content, antioxidant activity through complementary methods (DPPH, FRAP, and ABTS) and enzymatic activity (bromelain, phenylalanine ammonia lyase (PAL) and polyphenol oxidase) were evaluated. Whole and wounded pineapple shell and core were dipped in a hot water bath at 30 ± 1 °C or 40 ± 1 °C for 10 min and stored under refrigeration conditions (4 ± 1 °C) for 24 h or 48 h. Results allowed that pineapple by-products reacted differently to the tested stresses. For the core, the application of wounding and heat treatment (40 °C) before storage (24 h) induced a synergistic effect on the accumulation of phenols (increased 17%) and antioxidant activity (422%). For the shell samples, the treatment that most increased the content of phenols (14%) and antioxidant activity (3845%) was heat treatment at 30 °C and storage for 48 h. Treatments that positively influenced the content of phenols and antioxidant activity of the samples did not affect the activity of bromelain or PAL. This study showed that proper abiotic stresses could increase the functional value of by-products.